Economic Change and Cultural Evolution: The Ultimate Influence of Human Cognitive Limitations - Daniel Bordonaba-Bosque; María A. González-Álvarez; Pedro C. Marijuán; Jorge Navarro (Social Sciences)
How cognitive limitations of individuals may affect the dynamics of cultural evolution under the effects of economic and technological forces is explored here. In particular, the extraordinary economic growth during the industrial and scientific revolutions of the last two centuries has been accompanied by an extraordinary acceleration of cultural changes. We will propose that these changes are due to competition, decay and replacement processes among the different kinds of cultural contents, ultimately resulting from our cognitive limitations. Different laws have been proposed recently for the decay of individualized cultural items and for the underlying competition processes, which will be discussed herein. With respect to the informational/cognitive limitations of individuals, the cognitive psychology views will be complemented—and somehow quantified—from the angle of the “social brain” or “sociotype” hypothesis. The generational phenomenon also emerges, by which differentiated generations develop a remarkable divergence in ways of life, aspirations, ideals, values, and often in the use of communication technologies. It is in this interactive individual–generational context of competitive processes that the acceleration of cultural change during the few last decades might be investigated by considering the vastly increased economic output and the widespread use of new communication technologies.